Герої-мігранти роману Юлії Крістевої «Meurtre à Byzance» у пошуках себе - Dzyk, Roman (Wydawnictwo Naukowe UPH, 2023)
Розглядається еміграція як один із найважливіших культурних факторів ХХ і початку ХХІ ст. Виокремлюються різноманітні форми еміграції, зокрема тип письменника-емігранта. Слідом за Едвардом Саїдом екзиль інтерпретується не тільки як трагедія, а й як джерело продуктивної сили. Акцентується, що центральним поняттям для дослідження екзилю виступає „чужість“. В цьому аспекті детально розбираються теоретичні погляди на феномени еміграції, вигнанництва й інакшості Юлії Крістевої, представлені у книзі Étrangers à nous-mêmes (Самі собі чужі, 1988), провідною думкою якої є те, що чужість іншого може бути сприйнята і прийнята тільки тоді, коли буде осмислена чужість самому собі. У якості художньої реалізації цих теоретичних поглядів розглядається роман Крістевої Meurtre à Byzance (Убивство у Візантії, 2004). Увага зосереджена на головних персонажах роману, які є емігрантами у другому, а то й у третьому поколінні. Їхнє осмислення власної інакшості й пошуки себе інтерпретуються як художнє відтворення своєрідного компенсаторного механізму, безпосередньо важливого для самої авторки. The article under studies deals with the issue of emigration as one of the most significant cultural factors of the XX and early XXI centuries. It outlines various forms of emigration, in particular, such a type as a migrant writer. Following the idea of Edward Said, it interprets exile not only as a human tragedy, but also as a source of efficient energy. Particular emphasis has been laid on the concept of “alienness”, which is generally regarded as a central notion in studying exile. In this respect, the article presents a detailed analysis of Julia Kristeva’s views on the concepts of migration, exile, and “otherness”, which are described in her book Étrangers à nous-mêmes (Strangers to Ourselves, 1988). The main idea of the book lies in the fact that “alienness” may be perceived and accepted only provided it is internally comprehended by a person. Kristeva’s novel Meurtre à Byzance (Murder in Byzantium, 2004) is considered as a fictional implementation of her views. Peculiar attention is focused on the main characters of the novel, who are emigrants in the second or even in the third generation. Their comprehension of their own otherness and search for themselves are interpreted as a fictional reproduction of a kind of compensatory mechanism that is directly important for the author herself.
Migrant Characters in Search of Themselves in the Novel by Julia Kristeva "Meurtre à Byzance"
Keywords: Юлія Крістева; еміграція; екзиль; чужість; Meurtre à Byzance; Julia Kristeva; emigration; exile; alienness; Murder in Byzantium